Assessment of fluoride level in drinking water sources in Sudurpaschim Province, Nepal - Joshi, Naresh Prasad; Joshi, Jagadish; Singh, Abanish (Journal of Nepal Health Research Council, 2024)
Background: Fluoride, a naturally occurring element found in varying concentrations in water, confers preventive effects in dental caries around a concentration of 1 ppm. The study aimed to assess the level of fluoride in drinking water sources in the Sudurpashchim Province of Nepal.Methods: A cross-sectional study was conducted from April to July 2023 with water samples from natural, municipal, and packaged sources collected in polypropylene plastic bottles from all 9 districts of the province. Three samples from each district's two most populous municipalities (one urban and one rural municipality) were taken. Water samples from the only sub-metropolitan city in the province (Dhangadhi) were also included. Fifty-seven samples were sent to a Nepal Standard-certified lab in Kathmandu for fluoride estimation using the American Public Health Association-approved method. Data were entered in Microsoft Excel and analysed using the Statistical Package for Social Sciences v 22. A p-value less than 0.05 was taken as significant. Results: Most of the water samples had fluoride levels below 0.1 ppm. The highest fluoride concentration was seen in a sample from a hand pump in the rural municipality of Kanchanpur (0.9 ppm). No significant differences were observed between water samples according to different water sources, geographical regions, or categories of water resources.Conclusions: Fluoride concentration in water sources of Sudurpashchim is well below the recommended level for caries protection. Measures should be taken to ascertain people get adequate fluoride as needed.Keywords: Fluoride; Nepal; sudurpashchim; water fluoridation; water sources.